Lana Turner : a Silver Valley childhood. - Nunn, Cynthia Ackley (Arcadia Publishing by arrangement with Fonthill Media, LLC, 2020)
The Sweater Girl, Queen of the Silver Screen, Lanita, Nightclub Queen--Lana Turner was known by many nicknames after her rise to fame, most of which she detested. Her private life, like her movies, played out before an audience of millions. Her numerous marriages and scandals became fodder for tongue-waggers and malicious gossip columnists. What many forget is that before she became Lana Turner, she was Julia Jean Turner, or simply Judy to the people who knew her as a child in the small mining town of Wallace, Idaho. Very little has been written about her earliest years as a child in Idaho's Silver Valley, which were probably some of the happiest and most formative of her life. Facts are hard to come by, but determined digging has brought some new information to light. Wallace is a town that is exceedingly proud of its history in general, and of Lana Turner in particular. This native daughter is still strong in the memories of the people of Wallace. She was theirs before Hollywood and the rest of the world claimed her.